Espressioni con monomi


Calcolare le seguenti espressioni

1       (2a2)(-3ab2)-(5ab)(-a2b2)+(8a6b6):(-2a3b4) =                      Soluzione
2       (- x2y3z3)3(-3x3yz)2(2x) + (-x3y3z3)3(2x2yz)3:(-x2yz) =                      Soluzione
3       (abc)(ab)(ac) -(a3)(2b2c2) + (a2b)(a3b2c3):(a2b2c)2 =                      Soluzione
4       [(x-2):y -(-xy-2)-(x-2)-3:(x5y2)](x2y) =                      Soluzione
5       x2mym:(xy)m + 3xm - 2[(xz)m(xy)m:zm]:(xy)m =                      Soluzione
6       am+nbn:[am(ab)n]+(ab2)2m:[(ab)m]2:b2m =                      Soluzione
7       (xn)2n - [( x2)n]n + [(a-n)-1]2n -3[(a2)n]n =                      Soluzione